2009
DOI: 10.5539/ass.v5n1p25
|View full text |Cite
|
Sign up to set email alerts
|

Western Tourists Perception of Malaysian Gastronomic Products

Abstract: Continual efforts have been made by international organizations to discover new tourism products and activities that have the opportunity of being marketed and promoted. Gastronomy has been identified as one of the new tourism product which is directly relevant to the Malaysian context. At present gastronomy is a valuable source of attracting tourists from all over the world and this has led to the empirical investigation on western tourists perception of Malaysian gastronomic products (food, beverages and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…East Asia conforms to this tendency (Horng and Tsai, 2010), exemplified by Hong Kong which is portrayed as a sophisticated and cosmopolitan city with an appropriate dining scene (Okumus et al, 2006). South East Asian countries are also promoting food-related tourist pursuits, led by Thailand (Rittichainuwat et al, 2001) and Malaysia (Jalis et al, 2009) as well as Singapore.…”
Section: Food and Touristsmentioning
confidence: 95%
“…East Asia conforms to this tendency (Horng and Tsai, 2010), exemplified by Hong Kong which is portrayed as a sophisticated and cosmopolitan city with an appropriate dining scene (Okumus et al, 2006). South East Asian countries are also promoting food-related tourist pursuits, led by Thailand (Rittichainuwat et al, 2001) and Malaysia (Jalis et al, 2009) as well as Singapore.…”
Section: Food and Touristsmentioning
confidence: 95%
“…Several studies have found tourists' overall perceptions, acceptance and enjoyment towards Malaysian food and cuisine are positive (Jalis, Zahari, Zulkifly, & Othman, 2009;Karim, Chua, & Salleh, 2010;Roozbeh, Ng, & Boo, 2013;Chi, Chua, Othman, & Karim, 2013). Nevertheless, the extent to what tourists really recognise and distinguish Malaysian cuisine remains questionable.…”
Section: Introductionmentioning
confidence: 94%
“…The sustainability of a business venture requires selfawareness of one's place in a complex system with the potential to create economic, social, and environmental wealth [55]. It is no different in the food industry; the business venture must be able to create, distribute, and retain value for all stakeholders [55][56][57]. A production company no longer views itself as separated from the system [55], but much join in common interests with partners and consumers to create a wide-reaching system of values [58][59][60].…”
Section: The Sustainability Of Traditional Riau Malay Foodmentioning
confidence: 99%